ROBUST MOTION CONTROLLER DESIGN FOR PRECISE TRACKING OF BALL SCREW DRIVEN POSITIONING SYSTEM - Anang, N.A.; Jamaludin, Z.; Abdullah, L.; Maharof, M.; Nordin, M.H. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
This paper presents the design and analysis of cascade NP/PI position controller for machine tools application. The proposed control structure is an enhancement over the classical cascade P/PI position controller whereby a nonlinear function was designed and embedded onto cascade P/PI controller scheme to add element of robustness to the controller characteristics. The controller design consisted of three steps, namely; design of speed loop, design of position loop, and design of the nonlinear function. Both the speed loop and the position loop were designed based on loop shaping method in frequency domain using gain margin and phase margin as design considerations. The controller gains were confirmed based on results of stability. Three parameters identified for the nonlinear function were rate of variation of nonlinear gain (KO), maximum value of error, (emax) and sampling frequency, (δ). The controller tracking performances were numerically analysed and validated on an XY feed table positioning system. Cascade NP/PI were found to produce superior tracking performance over cascade P/PI controller with improvement in tracking performance of 6.63% and 15.63% at reference tracking frequencies of 0.4Hz and 0.7Hz respectively.